High lipid diet can keep liver health but cause muscle oxidative stress of triploid rainbow trout treated with acute hypoxic challenge - Changye Li; Buying Han; Guoliang Sun; Haining Tian; Zezhong Wu; Changzhong Li; Yuqiong Meng; Rui Ma (Aquaculture Reports)
Triploid rainbow trout (Oncorhynchus mykiss) is a hypoxia-sensitive and fatfish species that can efficiently utilize high-lipid diet (up to 30 %). In the study, two isonitrogenous diets with a lipid level of 23 % (normal control, NC) and 30 % (high lipid, HL), respectively, were fed to triploid rainbow trout with initial average weight of 233 g for 80 days, and then subjected to an acute hypoxic challenge, and estimated the effect of HL diet on acute hypoxic tolerance of triploid rainbow trout. The results showed that 1) HL diet significantly increased plasma lactate dehydrogenase, glucose, total cholesterol, high and low density lipoprotein cholesterol levels, but decreased alanine aminotransferase level (P < 0.05). 2) HL diet did not affect hepatic malondialdehyde (MDA) content (P > 0.05), while it significantly increased MDA content in the plasma and muscle (P < 0.05). Antioxidant gene expression in the liver were upregulated, but some genes expression in the muscle were downregulated in the HL group. 3) HL diet significantly increased inflammatory and immune genes expression in the liver and muscle (P < 0.05), and the increase is more pronounced in the muscle. 4) HL diet activated lipolysis, autophagy and gluconeogenesis related genes expression, but inhibited lipid synthesis and glycolysis related genes expression. In summary, HL diet could promote hepatic lipolysis to supply energy, enhance hepatic antioxidant, and then alleviate liver damage caused by oxidative stress when fish was treated with acute hypoxic challenge. However, the diet could aggravate muscular oxidative stress and inflammation, and then result in muscle damage.